In vitro blood cell viability profiling of polymers used in molecular assembly - Jeong, Hyejoong (Sci Rep, 2017)
Biocompatible polymers have been extensively applied to molecular assembly techniques on a micro- and nanoscale to miniaturize functional devices for biomedical uses. However, cytotoxic assessments of developed devices are prone to partially focus on non-specific cells or cells associated with the specific applications. Thereby, since toxicity is dependent on the type of cells and protocols, we do not fully understand the relative toxicities of polymers. Additionally, we need to ensure the blood cell biocompatibility of developed devices prior to that of targeted cells because most of the devices contact the blood before reaching the targeted regions. Motivated by this issue, we focused on screening cytotoxicity of polymers widely used for the layer-by-layer assembly technique using human blood cells. Cytotoxicity at the early stage was investigated on twenty types of polymers (positively charged, negatively charged, or neutral) and ten combination forms via hemolysis, cell viability, and AnnexinV-FITC/PI staining assays. We determined their effects on the cell membrane depending on their surface chemistry by molecular dynamics simulations. Furthermore, the toxicity of LbL-assembled nanofilms was assessed by measuring cell viability. Based on this report, researchers can produce nanofilms that are better suited for drug delivery and biomedical applications by reducing the possible cytotoxicity.